Defending the Environment: Civil Society Strategies to Enforce International Environmental Law - Malone Linda A. (Island Press, 2006)
Defending the Environment provides the means for nongovernmental organizations, community groups, and individuals to bring environmental and public health problems to the attention of international courts, tribunals, and commissions, or to their domestic counterparts. It suggests specific strategies and provides detailed information for taking action. This revised and updated edition also contains new case studies of the application of those strategies that has occurred in recent years.